Impact of transurethral resection of the prostate on erectile function in benign prostatic hyperplasia patients: a descriptive study at a tertiary care hospital - Farhan Khan; Soomro, Naveed; Sarwar, Muhammad Adnan; Aslam, Muhammad Mashkoor; Haider Ali Qureshi; Murtaza, Hafiz Bilal (Journal of University Medical & Dental College, 2024)
Background & Objective: Benign prostatic hyperplasia (BPH) is a prevalent condition in older males, primarily responsible for lower urinary tract symptoms (LUTS). Transurethral resection of the prostate (TURP), a frequently utilized surgical procedure for BPH management, has mixed effects on erectile function (EF). The objective of this study is to evaluate the changes in EF following TURP in patients with BPH. Methodology: This descriptive study was conducted at Bilawal Medical College for Boys, LUMHS Jamshoro, involving 261 male subjects between the ages of 50 and 70 who underwent TURP. Evaluation of EF was carried out before and after the surgical procedure using the International Index of Erectile Function (IIEF) scoring system. RESULTS: The average age of the participants was 60.47 years, and the mean duration of BPH prior to surgery was 15.83 months. The mean IIEF score prior to surgery was 16.72, which notably decreased to 11.50 after surgery. This decline was statistically significant (p < 0.001), and this trend remained consistent across variables such as age, duration of BPH, and prostate volume. Conclusion: The study concludes that TURP significantly correlates with a decline in EF among patients with BPH. These outcomes highlight the necessity for comprehensive preoperative counseling about the potential impacts on sexual health for patients considering TURP.